The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1988
DOI: 10.1002/etc.5620070506
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine and mercury residues in wild mink and otter: Comparison with fish

Abstract: Organochlorine and mercury levels in wild mink (Mustela vison) and otter (Lutra canadensis) from eight areas of New York State were measured in adipose and liver tissues. Polychlorinated biphenyl (PCB) compounds, quantified as Aroclor 1254/1260 and p,p'‐DDE, were detected in all animals. Significantly greater concentrations of organochlorines in both species were associated with habitat known to be contaminated with PCB (Hudson Valley and within 5 mi of Lake Ontario). Wet‐weight PCB concentrations in adipose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…(Stejskal et al 1989). Mercury concentrations in liver tissue of Illinois mink are lower than those reported from wild mink in New York (Foley et al 1988) but similar to those reported in liver, kidney and muscle tissue from wild mink collected in less polluted regions of Ontario (Wren et al 1986). Mercury concentrations in liver tissue of Illinois mink are lower than those reported from wild mink in New York (Foley et al 1988) but similar to those reported in liver, kidney and muscle tissue from wild mink collected in less polluted regions of Ontario (Wren et al 1986).…”
Section: Discussionsupporting
confidence: 72%
“…(Stejskal et al 1989). Mercury concentrations in liver tissue of Illinois mink are lower than those reported from wild mink in New York (Foley et al 1988) but similar to those reported in liver, kidney and muscle tissue from wild mink collected in less polluted regions of Ontario (Wren et al 1986). Mercury concentrations in liver tissue of Illinois mink are lower than those reported from wild mink in New York (Foley et al 1988) but similar to those reported in liver, kidney and muscle tissue from wild mink collected in less polluted regions of Ontario (Wren et al 1986).…”
Section: Discussionsupporting
confidence: 72%
“…For example, fatty acid signatures and carbon and nitrogen stable isotopes in herring gulls sampled between 1978 and 2005 have indicated a decline in fi sh consumption, and this corresponded well with decreased levels of contaminants in their eggs (Hebert et al 2008 ) . Others have reported that varying levels of mercury in local prey fi sh relate well with mercury levels in mink and river otter tissues (Cumbie 1975 ;Kucera 1983 ;Wren et al 1986 ;Foley et al 1988 ) .…”
Section: Environmental Exposures To Methylmercurymentioning
confidence: 96%
“…As top level piscivorous predators, osprey (Pandion haliaetus), otter (Lutra sp.) and mink are generally considered to be representative barometers of aquatic/semi-aquatic ecosystem health [10,[64][65][66][67][68][69][70][71]. Interestingly, the use of mink and otter as sentinels/bio-indicators or related sample types, as both pertain to factors such as contaminant body burden, have been called into question [72,73].…”
Section: Case Study 1: Chronic Exposure Of River Otters To Nsaids In mentioning
confidence: 99%